The biographical dimension in continuing teacher education: transformations and complexities (Revista Internacional de Formação de Professores, 2024)
The aim of this article is to understand how teachers relate to their memories, signifying and shaping their experiences, building an awareness of themselves and their learning throughout their life journey and formation, through the processes of biographical reflection. To this end, it delved into relevant concepts through a literature review and analyzed interviews conducted as part of the PERFORMA project. The interviews are part of a collection made up of audio recordings and written narratives from a project that carries out formative courses with public school teachers. The non-chronological nature of the narratives is highlighted, as is the potential link produced by biographical activity, the temporality of memory and the formative nature of biographical narrative as a tool in teacher education. We conclude that the biographical dimension in continuing teacher education is a useful tool for understanding various aspects of teachers' lives, and also contributes as a formative tool.
Keywords: Biography. Life story. Teacher education. Psychology. Identity.